The Shape of the Vocabulary Predicts the Shape of the Bias - Perry, Lynn K.; Samuelson, Larissa K. (Frontiers in Psychology, 2011)
Children acquire attentional biases that help them generalize novel words to novel objects. Researchers have proposed that these biases arise from regularities in the early noun vocabulary children learn and suggest that the specifics of the biases should be tied to the specifics of individual children’s vocabularies. However, evidence supporting this proposal to date comes from studies of group means. The current study examines the relations between the statistics of the nouns young children learn and the similarities and differences in the biases they demonstrate. We show that individual differences in vocabulary structure predict individual differences in novel noun generalization. Thus, these data support the proposal that word-learning biases emerge from the regularities present in individual children’s vocabularies and, importantly, that children’s online attention during an experiment is mediated by instances of past learning.